Analisis Risiko Kredit Usaha Kecil dan Menengah (UKM) pada Platform Pinjaman Berbasis Daring - Amir Fatahuddin; Shinta Permata Sari; Alif Akbar Subikhi (Prosiding University Research Colloquium, 2020)
The development of online-based loans defined as Peer to Peer (P2P) Lending provides an opportunity for Small and Medium Enterprises (SMEs) to obtain funds with an easier process. There are several factors that influence lending decisions by lenders and make their loan applications are being fulfilled. This study aims to analyze the factors that effect lending decisions on the Peer to Peer (P2P) Lending platform by considering credit risk: loan amount, interest rate, term loan, loan purpose, and credit rating. The data obtain through the Investree platform, one of the most developed Peer to Peer (P2P) service providers in Indonesia and licensed by Financial Services Authority (OJK). The sample’s method is judgement sampling and data analyze using logistic regression. The results show that loan amount and credit rating have effect on lending decisions, meanwhile interest rate, loan term, and loan purpose have no effect on lending decision.